In Forest and Intact: Designating Future Use of Family-Forest-Owned Land. Issue 4 (29th June 2018) - Markowski-Lindsay, Marla; Catanzaro, Paul; Bell, Kathleen; Kittredge, David; Markowitz, Ezra; Leahy, Jessica; Butler, Brett; Milman, Anita; Allred, Shorna
Abstract: Much of the family-forest-owned land in the United States is expected to change hands as current ownerships grow older and pass on their holdings. To date, little research has been conducted on this ownership decision. Using mail survey data from the northeastern United States, we explore family-forest-owner (FFO) legacy planning. We summarized FFO interest in planning for the future use of their land. We found that nearly 50% of respondents believe that controlling future use of their land is important; and one-half to two-thirds of respondents are open to keeping most or all of their land forested and undivided. We investigated legacy priorities influencing FFO intentions and decisions to control use. FFO intentions to keep their land in forest use and intact have significant influence on designating future use. Further, FFOs have distinct legacy goals that significantly influence intention and behavior to designate future use of their land.